KEPASTIAN HUKUM AKTA PENDIRIAN PERSEROAN KOMANDITER (COMMANDITAIRE VENNOOTSCHAP) YANG TIDAK DIUMUMKAN DALAM BERITA NEGARA DITINJAU DARI KITAB UNDANG-UNDANG HUKUM DAGANG - DANIEL DUHA (PREMISE LAW JURNAL, 2016)
DOSEN PEMBIMBING:Muhd YaminT. Keizerina Devi ASyahril Sofyan Limited partner or what it is usually called Commanditaire Vennootschap (CV) is a company which is established by one or more persons jointly and severally with one or more persons as limited partner as it is stipulated in Article 19 of KUHD (Code of Commercial Law). There is no specific provision in KUHD about the method of establishing it because CV is a business firm so that Article 22 of KUHD can be used. Therefore, CV is established by Memorandum of Association which is made before a Notary and registered'in the Clerk of the District Court, and the excerpt is announced in the State Gazette. The problems of the research were as follows: how about the legal domicile of CV which is not announced in the State Gazette, how about the responsibility of the CV management which Memorandum of Association is not announced in the State Gazette, and the problem of the establishment of CV in a Notary's daily practice. The research used judicial normative method, a doctrinaire law which is referred to legal norms in the KUHD. Therefore, this research emphasized on secondary legal materials, either regulations or judicial theories. Legal domicile of Memorandum of Association of a CV which is not announced in the State Gazette is valid, but the CV is considered only as a business firm. Therefore, any action done by limited partner toward the third party is considered as a general action; it is considered as being established in uncertain time without one of the limited partners is exempted from it. When a CV is not announced in the State Gazette, it is considered as the same position as a business firm as it is the same as active partner. Therefore, the responsibility of limited partner and active partner is similar; that is unlimited (full) responsibility, and any relationship with the third party is a collective responsibility. A Notary is often involved in drawing up Memorandum of Association of a CV outside his notarial position, and he is often faced by married couples' appearing in drawing up Memorandum of Association of a CV. Keywords : Memorandum of Association of Limited Partner (Commanditaire Vennootschap)